Prognostic Model for Predicting Survival in Patients with Disease Recurrence Following Radical Cystectomy - Kluth, Luis A; Xylinas, Evanguelos; Rieken, Malte; Kent, Matthew; Ikeda, Masaomi; Matsumoto, Kazumasa; Hagiwara, Masayuki; Kikuchi, Eiji; Bing, Megan T; Gupta, Amit; Sewell, Joseph M; Konety, Badrinath R; et al. (European urology focus, 2015)
BACKGROUND: Although the natural history of urothelial carcinoma of the bladder (UCB) from radical cystectomy (RC) to disease recurrence (DR) has been investigated intensively, the course of patients who have experienced DR after RC for UCB remains poorly understood. OBJECTIVE: To evaluate the prognostic value of the Bajorin criteria that consists of two risk factors: Karnofsky performance status (KPS) and the presence of visceral metastases (VMs) in patients with DR after RC for UCB. Furthermore, to identify additional factors associated with cancer-specific mortality (CSM) and thus build a multivariable model to predict survival after DR. DESIGN, SETTING, AND PARTICIPANTS: We identified 967 patients with UCB who underwent RC at 17 centers between 1979 and 2012 and experienced DR. Of these, 372 patients had complete data we used for analysis. OUTCOMES MEASUREMENTS AND STATISTICAL ANALYSIS: Univariable Cox regressions analysis was performed. We used a forward stepwise selection process for our final multivariable model. RESULTS AND LIMITATIONS: Within a median follow-up of 18 mo, 266 patients died of disease. Cancer-specific survival at 1 yr was 79%, 76%, and 47% for patients with no (n=105), one (n=180), and two (n=87) risk factors (p<0.001; c-index: 0.604). On multivariable analyses, we found that KPS <80%, higher American Society of Anesthesiologists score, anemia, leukocytosis, and shorter time to DR (all p values <0.034) were independently associated with increased CSM. The combination of time to DR and KPS resulted in improved discrimination (c-index: 0.694). CONCLUSIONS: We confirmed the prognostic value of KPS and VMs in patients with DR following RC for UCB. We also found several other clinical variables to be associated with worse CSM. We developed a model for predicting survival after DR inclusive of time to DR and KPS assessed at DR. If validated, this model could help clinical trial design. PATIENT SUMMARY: We developed a model to predict survival following disease recurrence after radical cystectomy for urothelial carcinoma of the bladder, based on time to disease recurrence and Karnofsky performance status.
Keywords: Transitional cell carcinoma; Bladder cancer; Disease recurrence; Survival; Metastasis; Prognosis; Model; Urothelial carcinoma of the bladder